Innovation in Hajj and Umrah - Albihany, Naeem Ali (The Arab Journal of Administration, 2024)
No one can deny the huge efforts and continuous improvement made by the Saudi government to make Hajj and Umrah an unforgettable event. In addition, the Government strongly supports all efforts to improve the quality of services provided to all Muslims, especially those visiting sacred places. One of the most obvious examples is the adoption of innovations, financing of research and studies, conducting annual forums and scientific conferences. This scientific study reviewed previous studies that linked innovation to Hajj and Umrah. The study aimed to achieve two purposes: first, to broaden our understanding of the extent and nature of research activities carried out on innovation in the Hajj and Umrah sectors, and second, to propose a road map for future studies. The study applied the scoping review methodology for the review of literature related to the concept of innovation and its relationship to Hajj and Umrah activities by relying on global data sources on the website of the Saudi Digital Library and reviewing studies in relevant English published between 2010 and 2022. The results of this review showed the paucity of studies discussing the topic of the study, and the researcher concluded that there were nine articles discussing the concept of innovation in Hajj and Umrah. Most of which used the qualitative approach by interviewing different stakeholders. The researcher then reviewed these articles, which varied between the health, commercial, educational and cultural sectors. Most of these studies were produced by Indonesia and Malaysia, and the study concluded with a number of future research ideas, and finally the most important determinants facing the study.